Target date funds and portfolio choice in 401(k) plans - Olivia S. Mitchell; Stephen P. Utkus (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
Target date funds in corporate retirement plans grew from 5B in 2000 to 734B in 2018, partly because federal regulation sanctioned these as default investments in automatic enrollment plans. We show that adopters delegated pension investment decisions to fund managers selected by plan sponsors. Including these funds in retirement saving menus raised equity shares, boosted bond exposures, curtailed cash/company stock holdings, and reduced idiosyncratic risk. The adoption of low-cost target date funds may enhance retirement wealth by as much as 50 percent over a 30-year horizon.
Keywords: D12; D14; D91; G41; G51; J32; 330; automatic enrollment; pension; portfolio allocation; endorsement effect; default effect; retirement saving